Knowledge and attitude towards cervical cancer among reproductive age group women in Gondar town, North West Ethiopia - Ayelign Mengesha; Anteneh Messele; Biruk Beletew (BMC, 2020)
Abstract Background Cervical cancer is the second most commonly diagnosed cancer and the third leading cause of cancer death in women worldwide. Nearly 83% of the world's new cases and 85% of all cervical cancer-related deaths occur in developing countries. It is primarily caused by human papilloma virus (HPV); a sexually transmitted pathogen that could be prevented with safe sexual practice and using vaccines among others. The aim of the study was to assess the knowledge and attitude of reproductive age group women towards cervical cancer and its prevention in Gondar town. Methods A descriptive community based cross-sectional study was carried out. An interviewer-administered questionnaire was employed for data collection. A multistage sampling technique was employed to select the study participants. Descriptive statistics like frequency, mean and percentage were computed using SPSS version 20 software program. Results Seven hundred and seventy women (n = 770) participated with a response rate of 100%. More than half, (65.1%) of the participants claim hearing of cervical cancer. However, majority (> 80%) of them lack knowledge that HPV is a causative agent of cervical cancer which is extremely worrying as the most important way to prevent cervical cancer is blocking HPV infection. Of those who had heard of it, only 107 (21.4%) said they have heard about Pap smear test. From them, less than half, 47 (43.9%) said that an apparently healthy woman should undergo the test at least three times in her life. This means in addition to the lack of information about the test, majority of those who had heard about it didn't know how many times they should have the test in their life. Overall, only 153 (19.87%) of the participants were found having a good knowledge of cervical cancer and its prevention. Conclusion The overall knowledge of women towards cervical cancer was inadequate. On the other hand, those who had heard about it had a somewhat encouraging attitude. Mass media was the major source of information. But, any public health problem cannot be solved in isolation. Hence, initiating large-scale awareness campaigns is recommended.